Challenges in doctoral supervision in South African universities - Akala, Benard Ungadi (Open Science Journal, 2021)
This article addresses the challenges encountered by doctoral supervisors as they interact with their doctoral students in the contexts of South African universities. In a qualitative study of seven doctoral (PhD) supervisors and six PhD students, data was collected using interviews to examine the challenges supervisors experience as they supervise doctoral students. The PhD students were included in this study in because their responses would confirm or refute supervisor's views/opinions that emanated from their experiences in a social, cultural, and political context. Data analysis showed that doctoral supervisors experienced multiple challenges including overworking, time, and a set of academic characteristics of PhD students. Overall, the results of this study suggest that certain aspects among doctoral students who have completed doctorates in South African context, and their supervisors in different parts of the world would provide a starting point in the understanding of the implications of these aspects and their effect on the selection of doctoral students and the ongoing research in doctoral supervision in the South African context. doctoral supervision.